Roles of 5,10-Methylenetetrahydrofolate Reductase C677T Polymorphisms in First-Episode, Drug-Naive Adult Patients With Depression - Li, Zhuoqing; He, Bo; Xu, Jian; Dai, Nan; Ping, Liangliang; Zhou, Cong; Shen, Zonglin; Xu, Xiufeng; Cheng, Yuqi (Frontiers in Psychiatry, 2020)
5,10-methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphism is considered as a predisposition and promising genetic candidate to major depressive disorder (MDD), as it is associated with impaired one-carbon cycle, which may involve in the pathogenesis of depression. Cortical thickness (CT) and subcortical structure volumes have been extensively studied in MDD, and have been proposed as one of the phynotypes for MDD. We intend to discuss the association between cortical thickness, subcortical structure volume and MTHFR C677T polymorphism in first- episode, treatment-naive patients with MDD. In this study, 127 adult patients with MDD, and 101 age-, and gender-, matched the healthy controls (HC) were included. All subjects underwent T1-weighted MRI, MTHFR C677T genotyping and FreeSurfer software-based morphological analysis. MDD patients have been detected significant decreased volumes in the left nucleus accumbens (P < 0.001). MTHFR 677 T allele carries manifested with thinner cortical thickness in the left caudal anterior cingulate cortex (cACC, P = 0.009) than CC genotype. There were significant genotype-by-diagnosis interactions for the cortical thickness in the left cACC (P = 0.009), isthmuscingulate (P = 0.002), medial orbitofrontal lobe (P = 0.012), posterior cingulate (P = 0.030), and the right lateral orbitofrontal lobe (P = 0.012). We also found a trend in interaction effect on the volume of the left putamen (P = 0.050). Our results revealed that MTHFR C677T polymorphism may be involved in the dysfunction of limbic-cortical-striatal-pallidal-thalamus (LCSPT) circuits mediating emotion processing, which may contribute to pathogenesis of MDD.